Academic Supervision Management In SD Negeri Tuntang 03 Semarang Regency - Warihadi, Gutomo; nurkolis, Nurkolis; Sulianto, Joko (International Journal Labs, 2024)
Teacher professionalism is an important factor in determining the quality of education. However, teacher professionalism needs to continue to be improved in accordance with the dynamics of needs. One effort to increase teacher professionalism is academic supervision. SDN Tuntang 03 Semarang Regency is a school that stands in the center of the Tuntang District government and there is an increase in the results of academic supervision every year. The focus of this research is how to plan, implement and follow up on academic supervision to increase teacher professionalism at SDN Tuntang 03 Semarang Regency. This research method is descriptive qualitative. located at SDN Tuntang 03 Semarang Regency. The research steps carried out were 1) carrying out pre-research, 2) compiling instruments and carrying out data collection (primary data and secondary data), 3) analyzing the data, 4) checking the validity of the data using triangulation. Research instruments are interviews, observation and documentation. Data analysis includes data collection, data reduction, data presentation and conclusions